The task of a science teacher is to create governance of the learning and emotional environment for elementary school students - Muhammad Dekar; Dinda Widyastika; Rudi Hermansyah Sitorus (Jurnal Scientia, 2024)
The aim of this research is to determine the task of science teachers in creating emotional management and learning environments for students, in the form of supporting or inhibiting factors for emotional management and learning environments. The type of research in qualitative descriptive research is using observation, interviews and documentation data collection techniques. The data analysis technique used is in the form of notes on the results of the interviewees, in this case science teachers. The research results show that emotional management can be said to be running well and under control. Meanwhile, the management of the learning environment at the Nurul Huda private sector, Medan Johor sub-district, Medan city, is quite good. This can be proven by optimizing the role of teachers in implementing the principles of structuring the learning environment both in the classroom and outside the classroom. Class management that is attractive, clean and tidy is the result of management by the teacher so that a conducive and fun learning atmosphere is created that supports the achievement of educational goals. The supporting and inhibiting factors for emotional management and the learning environment are internal and external factors. Teaching staff, students, facilities (school buildings), are internal factors. Meanwhile, the community environment, family, thoughts, behavior and personality are external factors.